1992
DOI: 10.1055/s-2006-961381
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic Activity of β-Damascenone andE-Phytol Isolated fromIpomoea pes-caprae

Abstract: The crude extract (IPA) of the plant Ipomoea pes-caprae (L.) R. Br. has previously been shown to antagonize smooth muscle contractions induced by several agonists via a non-specific mechanism. Bioassay-guided fractionation of IPA resulted in isolation of the antispasmodically acting isoprenoids beta-damascenone and E-phytol. Their antispasmodic potencies were found to be in the same range as that of papaverine, a general spasmolytic agent. This effect was suggested to play a role in the previously observed ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 7 publications
1
65
0
1
Order By: Relevance
“…Bioassay guided fractionation of this extract resulted in isolation of the isoprenoids E-phytol and β-damascenone. The antispasmodic potencies of these compounds were found to be in the same range as that of papaverine, a known spasmolytic agent (Pongprayoon et al, 1992a). However, similar study with the plant collected in Brazil showed differece in terms of the chemical composition and did not showed antispasmodic activity when tested on isolated guineapig ileum and rat duodenum (Emendorfer et al, 2005).…”
Section: Ipomoea Parasitica (Kunth) G Donmentioning
confidence: 93%
“…Bioassay guided fractionation of this extract resulted in isolation of the isoprenoids E-phytol and β-damascenone. The antispasmodic potencies of these compounds were found to be in the same range as that of papaverine, a known spasmolytic agent (Pongprayoon et al, 1992a). However, similar study with the plant collected in Brazil showed differece in terms of the chemical composition and did not showed antispasmodic activity when tested on isolated guineapig ileum and rat duodenum (Emendorfer et al, 2005).…”
Section: Ipomoea Parasitica (Kunth) G Donmentioning
confidence: 93%
“…Since endothelial cell contraction increases vascular permeability, and since this permeability is inhibited by vasodilating agents, the antispasmodic activity of I. pescaprae can be assumed to contribute to the anti-inflammatory action of this plant (6). The cited investigators based their hypo-thesis on the tentative theory that endothelial cell contraction causes increased vascular permeability and on the fact that agents such as ß-adrenoceptor agonists and calcium antagonists inhibit this permeability with general relaxant properties.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study has reported an analgesic effect of this extract (5). In addition, other species of the family Convolvulaceae such as I. pes-caprae also have been reported to have anti-inflammatory, antispasmodic and antihemolytic properties (6).…”
Section: Introductionmentioning
confidence: 91%
“…This plant stabilized sand dunes and prevented coastal erosion (Hill, 2001) and used in folk remedies for different types of ailments (Ganjir et al, 2013). Pharmacological profiling of the plant showed the following activities: antioxidant (Ramanathan et al, 2012;Parekh et al, 2012), analgesic (De Souza et al, 2000;Bragadeeswaran et al, 2010;Rajamoni, 2010;Vieira et al, 2012), anti-inflammatory (Vieira et al, 2012;Venkataraman et al, 2013a;Pongprayoon et al, 2006), antispasmodic (Pongprayoon et al, 1992), antinociceptive (Vieira et al, 2012;Krogh et al, 1999;De Souza et al, 2000), antiarthritic (Venkataraman et al, 2013b), antihistaminic (Wasuwat, 1970), insulinogenic and hypoglycemic activities (Khan et al, 1994), antifungal -Candida albicans and Microsporum audouinni (Ramanathan et al, 2011) and immunostimulatory (Philippi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This area has a warm humid temperate climate with hot summers and no dry season (Weather Spark beta, 2012). Conversely, Pongprayoon et al (1992) in Sweden, had isolated antispasmodically acting isoprenoids betadamascenone and E-phyto. Most parts of Sweden are icebound in winter, but experience elevated temperature ranging from 13 0 C to 17 0 C in the month of July (WeatherOnline, 2013).…”
Section: Introductionmentioning
confidence: 99%